2015
DOI: 10.1002/2015gl066007
|View full text |Cite
|
Sign up to set email alerts
|

a, b careful: The challenge of scale invariance for comparative analyses in power law models of the streamflow recession

Abstract: The falling limb of the hydrograph—the streamflow recession—is frequently well approximated by power law functions, in the form dq/dt = −aqb, so that recessions are often characterized in terms of their power law parameters (a, b). The empirical determination and interpretation of the parameter a is typically biased by the presence of a ubiquitous mathematical artifact resulting from the scale‐free properties of the power law function. This reduces the information available from recession parameter analysis an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 43 publications
2
63
0
1
Order By: Relevance
“…This is a consequence of a mathematical artifact that impacts fitted values of the recession scale parameter, arising when fitting power laws to datasets with arbitrarily chosen scaling (Dralle et al, 2015). The issue can be avoided by setting the recession exponent to a fixed value (e.g., the median; Biswal and Marani, 2010), but this comes at the expense of biasing the fitted values of a due to constraints on the exponent.…”
Section: Methods Combination Comparisonsmentioning
confidence: 99%
See 3 more Smart Citations
“…This is a consequence of a mathematical artifact that impacts fitted values of the recession scale parameter, arising when fitting power laws to datasets with arbitrarily chosen scaling (Dralle et al, 2015). The issue can be avoided by setting the recession exponent to a fixed value (e.g., the median; Biswal and Marani, 2010), but this comes at the expense of biasing the fitted values of a due to constraints on the exponent.…”
Section: Methods Combination Comparisonsmentioning
confidence: 99%
“…Recently, several authors have attributed physical meaning to observed variability across individual recessions within a single catchment, triggering an increase in event-scale recession analyses (Dralle et al, 2015(Dralle et al, , 2016Ghosh et al, 2016;Ye et al, 2014;Wittenberg, 1999;Marani, 2010, 2014;Biswal and Nagesh, 2014;Harman et al, 2009;Mutzner et al, 2013;Bart and Hope, 2014;Shaw, 2016;Patnaik et al, 2015;Shaw and Riha, 2012;Vogel and Kroll, 1996;Chen and Krajewski, 2016). Whereas classical, lumped recession analysis seeks a single recession model parameterization to describe all hydrograph recessions for an individual catchment, the goal of event-scale recession analysis is to interpret variations in catchment response to rainfall as a function of the properties of rainfall events (e.g., Harman et al, 2009) or the catchment state (e.g., Biswal and Marani, 2010;Shaw and Riha, 2012).…”
Section: N Dralle Et Al: Event-scale Recession Analysis Uncertaintymentioning
confidence: 99%
See 2 more Smart Citations
“…the exponent β can vary with the chosen methodology [Rupp and Selker, 2006;Stoelzle et al, 2013;Dralle et al, 2015;Thomas et al, 2015], spatial variation of rainfall and groundwater discharge [Biswal and Nagesh Kumar, 2014], and the quality of data [Rupp and Selker, 2006;Stoelzle et al, 2013]. Questions still remain about whether the α parameter is a meaningful way to summarize recession behavior.…”
Section: /2016gl067927mentioning
confidence: 99%